The Effect of BML-111 in Preeclampsia Rat Model Induced by the Low Dose of Cadmium Chloride - Zhang, KeKe; Hu, Min; Zhang, Lin; Zhang, Qiong; Huang, Yinping (American Journal of Perinatology Reports, 2019)
Aim This article determines the optimal time and dose of cadmium chloride (CdCl2) injected to pregnant rat to establish experimental preeclampsia (PE) model. In addition, the therapeutic potential of BML-111, a lipoxin A4 analogue, in the CdCl2-induced PE model was also evaluated.Methods Peritoneal injection of two dose of CdCl2 for successive 6 days was tested in the pregnant rats starting from various gestational days (GDs). During this process, the systolic blood pressure and the body weight of pregnant rats and neonatal rats were monitored. The pathological changes of the placenta and kidney were evaluated by hematoxylin and eosin staining. The phosphorylation of extracellular signal-regulated kinase 1/2 and signal transducer and activator of transcription 3 in the placentas was detected by Western blot, and the messenger ribonucleic acid expression of interleukin (IL)-6, tumor necrosis factor-α, and IL-10 in the placentas were detected by real-time polymerase chain reaction. BML-111 at the dose of 1 mg/kg/day was peritoneally injected into the rat after establishing the PE model to test its therapeutic potential.Results In the present study, we successfully established the PE model in pregnant rats by intraperitoneally injection of CdCl2 at the dose of 0.125 mg/kg/day from GD 9 to 14. We recapitulated multiple features of clinical PE in CdCl2-induced rat, including high blood pressure, renal dysfunction, and inflammatory response in placenta. Furthermore, treatment with BML-111 significantly relieved multiple features in our PE rat model.Conclusions BML-111 has a potential therapeutic effect in pregnant rats with CdCl2-induced PE, which appears to be mediated through inhibition of inflammatory processes in the placenta.
Keywords: preeclampsia; BML-111; cadmium chloride; inflammation